Protection of Women’s Rights in the Escalating Conflict in Palestine - Nidatya, Nurfarah; Darmastuti, Shanti; Saraswati, Dini Putri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The Israeli-Palestinian conflict is inextricably linked to the issues Palestinian women face. They have been affected psychologically, mentally, and physically. The Palestinian independence movement and Palestinian women's struggle are inextricably linked. The protection of women's rights has grown in importance in light of the protracted conflict in Palestine. Conflict-related tensions and economic pressures are contributing to an increase in domestic violence. In conflict areas, fundamental rights like freedom of speech, travel, and political participation are often ignored or restricted. This study investigates how both governmental and non-governmental entities safeguard women's rights in Palestine. This qualitative case study-based research examines how women's rights were maintained in Palestine as the conflict escalated. This study examines the dynamics of women's rights issues in Palestine and the difficulties in addressing these issues in-depth using secondary data from earlier studies, journal articles, and online articles. The study concludes that a multifaceted approach is necessary to protect women's rights in Palestine, given the Israeli occupation and patriarchal norms. Cooperation is required to defend women's rights and promote a more equitable society in Palestine.